Elevated Plasma Complement C1q Levels Contribute to a Poor Prognosis After Acute Primary Intracerebral Hemorrhage: A Prospective Cohort Study - Wang, Zefan; Wu, Xiaoyu; Yan, Tian; Liu, Ming; Yu, Wenhua; Du, Quan; Hu, Wei; Zheng, Yongke; Zhang, Zuyong; Wang, Keyi; Dong, Xiaoqiao (Frontiers in Immunology, 2022)
Objective The complement cascade is activated early following intracerebral hemorrhage (ICH) and causes acute brain injury. We intended to explore the effects of plasma complement component 1q (C1q) levels on hemorrhagic severity and functional outcome in ICH patients. Methods In this prospective cohort study, we measured the plasma C1q levels of 101 ICH patients and 101 healthy controls. The Glasgow Coma Scale (GCS) score and hematoma volume were used to assess the ICH severity. Poor prognosis was referred to as a Glasgow Outcome Scale (GOS) score of 1-3 at three months following a stroke. A multivariate logistic regression model was configured to determine the independent relation of plasma C1q levels to severity and poor prognosis. Under receiver operating characteristic (ROC) curve, prognostic capability of plasma C1q levels was evaluated. Results There was a significant elevation of plasma C1q levels in patients, as compared to controls [median (percentiles 25th-75th), 225.04 mg/l (156.10-280.15 mg/l) versus 88.18 mg/l (70.12-117.69 mg/l); P<0.001]. Plasma C1q levels of patients were independently related to GCS score (t =-3.281, P=0.001) and hematoma volume (t = 2.401, P=0.018), and were highly correlated with the GOS score at 3 months post-stroke (r=-0.658, P<0.001). Plasma C1q levels were obviously higher in poor prognosis patients than in other remainders (median percentiles 25th-75th), 278.40 mg/l (213.81-340.05 mg/l) versus 174.69 mg/l (141.21-239.93 mg/l); P<0.001). Under the ROC curve, plasma C1q levels significantly discriminated the development of poor prognosis (area under ROC curve 0.795; 95% confidence interval, 0.703–0.869; P<0.001). Using maximum Youden method, plasma C1q levels > 270.11 mg/l distinguished patients at risk of poor prognosis at 3 months with 56.52% sensitivity and 94.55% specificity. Meanwhile, the prognostic predictive ability of plasma C1q levels was equivalent to those of GCS score and hematoma volume (both P>0.05). Moreover, plasma C1q levels > 270.11 mg/l independently predicted a poor prognosis at 3 months (odds ratio, 4.821; 95% confidence interval, 1.211-19.200; P=0.026). Conclusion Plasma C1q levels are closely related to the illness severity and poor prognosis of ICH at 3 months. Hence, complement C1q may play an important role in acute brain injury after ICH and plasma C1q may represent a promising prognostic predictor of ICH.